Barriers to Sustainable Finance in Islamic Banking: Qualitative Insights from Bank Syariah Indonesia - Alifi, Awaliyah; Agung, Wahyu Dwi (MALIA: Journal of Islamic Banking and Finance, 2026)
Sustainable reporting aims to promote transparency and accountability, yet a significant implementation gap persists within the Indonesian Islamic banking sector. This study investigates the systemic barriers hindering the growth of sustainable financing at Bank Syariah Indonesia (BSI), where documented proportions decline between 2021 to 2023. Employing a qualitative methodology, the research synthesizes BSI’s annual reports with in-depth interviews from bank executives, entrepreneurs across various scales, sustainable financing expert, and the Financial Services Authority (OJK. The findings reveal three primary obstacles: first, a traditional credit framework within BSI that prioritize immediate profitability over ESG metrics. Second, an advisory regulatory stance by the OJK that lacks tangible fiscal incentives or infrastructure. Third, a misalignment between policy and practice that causes  entrepreneurs to perceive sustainable practises as a financial and administrative burden rather than a strategic advantage. By exposing the disconnect between government regulation and practical application, this study offers novel qualitative insights into the industry’s reality. It proposes targeted recommendations to harmonize the tripartite interest of the state, financial institutions, and the private sectors. Furthermore, the research advocates for integrating environmental protection (hifz al bi’ah ) into Sharia compliance to transition sustainability from a voluntary formality into a strategic pillar of operational stability. Ultimately, these strategies aim to enhance regulatory frameworks and foster innovation, supporting a more responsible and inclusive financial ecosystem aligned with global environmental goals.